Identification of soluble forms of the fibroblast growth factor receptor in blood. - Hanneken, A (1994)
We have purified three acidic (FGF-1) and basic (FGF-2) fibroblast growth factor binding proteins (FGF-BP1, FGF-BP2, and FGF-BP3) from human plasma and calf serum and demonstrate the presence of these circulating FGF-BPs in blood. Each are truncated forms of the high-affinity FGF receptor (FGFR-1). FGF-BP1 and FGF-BP2 have estimated molecular masses of 70-85 kDa and 55-60 kDa, respectively, and are detected by using 125I-labeled FGF-2 ligand blotting. Immunoblotting with four distinct antibodies to FGFR-1 reveals that FGF-BP1 and FGF-BP2 are immunologically and biochemically related to the extracellular domain of FGFR-1. Reverse-phase HPLC chromatography resolves FGF-BP2 into two proteins with estimated molecular masses of 55 kDa and 60 kDa. Protein sequencing of the amino terminus of FGF-BP2 and FGF-BP3 reveals identity with the extracellular domain of the two-IgG-loop form of human FGFR-1. The FGF-BPs do not require heparin to bind FGF-2 on affinity columns, but heparin does enhance their recovery from blood. These FGF-BPs may play an important physiological role in regulating the biological activity of FGF and the other members of the FGF family of growth factors.